Food materials science and engineering - Bhandari, Bhesh; Roos, Yrjo H. (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
'Food Materials Science and Engineering covers a comprehensive range of topics in relation to food materials, their properties and characterisation techniques, thus offering a new approach to understanding food production and quality control'--
Includes bibliographical references and index.
Keywords: Food -- Composition; Food -- Analysis